The Gut Entomotype of Red Palm Weevil Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae) and Their Effect on Host Nutrition Metabolism - Muhammad, Abrar; Fang, Ya; Hou, Youming; Shi, Zhanghong (Frontiers in Microbiology, 2017)
For invasive insects, the potential roles of gut microbiota in exploiting new food resources and spreading remain elusive. Red palm weevil (RPW), Rhynchophorus ferrugineus Olivier, is an invasive destructive pest which feeds on nutrient-poor tender tissues and has caused extensive mortality of palm trees. The microbes associated with insects can improve their nutrition assimilation. However, experimental evidence on the interactions between RPW and its gut microbiota is still absent. The aim of this study is to determine the dynamics changes and the bacterial entomotype in the RPW gut and its potential physiological roles. Here, we confirmed RPW harbors a complex gut microbiota mainly constituted by bacteria in the families Enterobacteriaceae, Lactobacillaceae, Entomoplasmataceae and Streptococcaceae. RPW gut microbiota exhibited a highly stable microbial community with low variance in abundance across different life stages and host plants. Furthermore, the abundance of Enterobacteriaceae was markedly increased but that of Acetobacteraceae was reduced significantly after administration of antibiotics. Although no significant effects were found on the body weight gain of RPW larvae, these alterations dramatically decreased the concentration of hemolymph protein and glucose while that of hemolymph triglyceride increased. In the gut of wild-caught RPW larvae, seven bacterial species in the genera Klebsiella, Serratia, Enterobacter and Citrobacter were shown to have an ability to degrade cellulose. Together, RPW accommodate a stable gut microbiota which can degrade plant polysaccharides and confer their host optimal adaptation to its environment by modulating its metabolism.